Pengaruh Risk Management dan Green Human Resource Management Practices terhadap Sustainable Employee Performance melalui Green Work Engagement pada Karyawan Perusahaan Bank BUMN di Balikpapan - Eka Nurjannah; Wiwiek Neviana Yusuf; Nanda Dian Eka; Wasti Sa'dan; Nurlia Nurlia (MES Management Journal, 2026)
This study aims to analyze the effect of Risk Management and Green Human Resource Management Practices on Sustainable Employee Performance through Green Work Engagement among employees of state-owned banks in Balikpapan. This research employed a quantitative approach with an associative design. Data were collected through questionnaires distributed to 280 respondents who were employees of state-owned banks in Balikpapan and were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS software. The results indicate that Risk Management and Green Human Resource Management Practices have a positive and significant effect on Green Work Engagement and Sustainable Employee Performance. In addition, Green Work Engagement was also found to have a positive and significant effect on Sustainable Employee Performance. The indirect effect testing further revealed that Green Work Engagement significantly mediates the relationship between Risk Management and Green Human Resource Management Practices on Sustainable Employee Performance. These findings confirm that effective risk management and the implementation of green-oriented human resource management practices play an important role in enhancing green work engagement and fostering sustainable employee performance in state-owned banks in Balikpapan.